Influence of the crystal packing in singlet fission: one step beyond the gas phase approximation. Issue 26 (14th May 2021) - Aguilar Suarez, Luis Enrique; de Graaf, Coen; Faraji, Shirin
Abstract : Singlet fission (SF), a multiexciton generation process, has been proposed as an alternative to enhance the performance of solar cells. Abstract : Singlet fission (SF), a multiexciton generation process, has been proposed as an alternative to enhance the performance of solar cells. The gas phase dimer model has shown its utility to study this process, but it does not always cover all the physics and the effect of the surrounding atoms has to be included in such cases. In this contribution, we explore the influence of crystal packing on the electronic couplings, and on the so-called exciton descriptors and electron–hole correlation plots. We have studied three tetracene dimers extracted from the crystal structure, as well as several dimers and trimers of the α and β polymorphs of 1, 3-diphenylisobenzofuran (DPBF). These polymorphs show different SF yields. Our results highlight that the character of the excited states of tetracene depends on both the mutual disposition of molecules and inclusion of the environment. The latter does however not change significantly the interpretation of the SF mechanism in the studied systems. For DPBF, we establish how the excited state analysis is able to pinpoint differences between the polymorphs. We observe strongly bound correlated excitons in the β polymorph which might hinder the formation of the 1 TT state and, consequently, explain its low SF yield.